2020
DOI: 10.1038/s41598-020-78209-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of salivary markers of kidney functions in acute and chronic kidney diseases

Abstract: Saliva can be used as an alternative diagnostic fluid enabling easy and non-invasive disease monitoring. Urea and creatinine can be measured in saliva and both were shown to be increased in renal failure. However, the dynamics of these markers during the development of kidney diseases is unknown. We aimed to describe the dynamics of salivary urea and creatinine in various animal models of acute kidney injury (AKI) and chronic kidney disease (CKD) and in patients with different stages AKI or CKD. Ninety Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Recently, many kidney damage-associated biomarkers that may be able to predict an AKI episode have been extensively reviewed, including Chitinase 3-like protein 1 (CHI3L1), Neutrophil gelatinase-associated lipocalin (NGAL), Kidney injury molecule-1, Liver fatty acid binding protein (L-FABP), osteopontin, hemojuvelin and interleukins [ 99 , 100 , 101 , 102 , 103 , 104 ].…”
Section: Predictors Of Renal Outcomesmentioning
confidence: 99%
“…Recently, many kidney damage-associated biomarkers that may be able to predict an AKI episode have been extensively reviewed, including Chitinase 3-like protein 1 (CHI3L1), Neutrophil gelatinase-associated lipocalin (NGAL), Kidney injury molecule-1, Liver fatty acid binding protein (L-FABP), osteopontin, hemojuvelin and interleukins [ 99 , 100 , 101 , 102 , 103 , 104 ].…”
Section: Predictors Of Renal Outcomesmentioning
confidence: 99%
“…Plasma biochemical analyses showed that SeBZF 3 did not cause changes in ALT and AST activities or urea levels as compared to the control group (Figure S1A–C). Certain chemical safety of SeBZF 3 is supposed from these assessments since their elevation can denote hepatocellular and kidney damage, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma biochemical analyses showed that SeBZF3 did not cause changes in ALT and AST activities or urea levels as compared to the control group (Figure S1A−C). Certain chemical safety of SeBZF3 is supposed from these assessments since their elevation can denote hepatocellular 45 and kidney damage, 46 respectively. In addition, parameters generally sensible to hazardous chemicals such as the body weight of the animals (Figure S1D), food intake (Figure S1E), and water consumption (Figure S1F) also remained without significant variations between the groups (Figure S1D).…”
Section: Sebzf3 Did Not Alter the Parameters Of Acutementioning
confidence: 99%
“…18 Previous work in humans determined that serum urea must meet a minimum threshold level before it diffuses into the saliva. 10 This may explain why the correlation coefficient was found to be moderate, but the test strip still performed well in detecting serum urea above the upper limit of the RI. Once the threshold is reached, urea begins to diffuse significantly into the saliva where it is detected by the saliva test strip to signal that azotemia is present.…”
Section: Discussionmentioning
confidence: 99%